ANALISIS TAKTIK PEMASARAN SYARIAH DALAM MENJARING MINAT NASABAH BMT EL-FAIRUZ - Ariana Savitri; Dinda Dwi Lestari; Dina Musthofia (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Over time, interest in the use of Islamic financial products is growing, especially in institutions related to banking. The increasingly fierce competition in the banking world encourages the Bank to continue to innovate in products and services in order to attract customers' interest. In this case, a marketing strategy is needed that must be continuously developed, especially in banking services, self-service, relational marketing tactics, relationship marketing, customer satisfaction and loyalty. The purpose of this study is to find out how the marketing strategy carried out by BMT El-Fairuz in attracting the interest of its customers. This research was conducted at BMT El-Fairuz because of the rapid development of BMT El-Fairuz, within 10 years it was able to have branches. In addition, it can be seen from the number of people from various circles who become customers at BMT El-Fairuz. This study uses a qualitative method with data collection techniques through the interview process. The results of this study are the marketing strategy carried out by BMT El-Fairuz in the form of a strategy through the diversity of products and locations used quite strategically, excellent and communicative service and promotional strategies that can attract customer interest in transactions.